Measurement of CP violation in the phase space of B±→K+K−π± and B±→π+π−π± decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2014)
The charmless decays B±→K+K−π± and B±→π+π−π± are reconstructed in a data set of pp collisions with an integrated luminosity of 1.0 fb−1 and center-of-mass energy of 7 TeV, collected by LHCb in 2011. The inclusive charge asymmetries of these modes are measured to be ACP(B±→K+K−π±)=−0.141±0.040 (stat)±0.018 (syst)±0.007(J/ψ K±) and ACP(B±→π+π−π±)=0.117±0.021 (stat)±0.009 (syst)±0.007(J/ψ K±), where the third uncertainty is due to the CP asymmetry of the B±→J/ψK± reference mode. In addition to the inclusive CP asymmetries, larger asymmetries are observed in localized regions of phase space.